The Role of Technological Innovation in Economic Growth of Angola's Agricultural Sector - da Silva, Augusto Lotti Joaquim Bié; Lambert, Edward; Deyganto, Kanbiro Orkaido (Archives of Business Research, 2025)
This study investigates the impact of technological innovation on economic growth in Angola’s agricultural sector from 2005 to 2023. The research focuses on how advancements in mechanization, irrigation systems, and improved seed varieties have contributed to productivity and overall GDP growth. Given the importance of agriculture in Angola’s economy, understanding the role of technology is essential for shaping future policies and investment strategies.A quantitative research approach was employed, using regression analysis to assess the relationship between GDP growth and five key factors: access to technology, education and training, financial support, government policies, and market demand. The study relies on historical data and economic indicators, evaluating trends over nearly two decades to establish a comprehensive understanding of technological innovation’s role in economic development.The results indicate a strong positive correlation between technological innovation and GDP growth in the agricultural sector. Increased mechanization and irrigation systems significantly enhanced farm productivity, while education and financial investment played a critical role in facilitating technology adoption. However, challenges such as policy inconsistencies and infrastructure limitations hindered the full potential of technological progress.These findings suggest that targeted investments in technology, improved education programs, and financial support are necessary to sustain agricultural growth. Additionally, policy reforms should address existing regulatory barriers, ensuring a stable and supportive environment for innovation. Strengthening rural infrastructure, including roads and electricity access, would further enhance the effectiveness of technological advancements.For Angola to maximize the benefits of technological innovation in agriculture, a multi-faceted approach is needed. Policymakers should focus on sustained investment, consistent regulations, and rural development initiatives. By addressing these key areas, Angola can improve agricultural productivity, increase food security, and drive long-term economic growth.